PSV-27 Fat color and myoglobin of meat from young cattle fed with mineral or concentrate in growing phase and finished on pasture or feedlot - Torrecilhas, Juliana A (J Anim Sci, 2019)
This trial aimed to evaluate the fat color and myoglobin concentration of three cattle breeds, supplemented in two nutritional plans (NP) during the growing phase and finished in the intensive system on pasture or conventional feedlot. One hundred and nineteen bulls from three genetic groups: Nellore (N), ½ Angus x ½ Nellore (A) and ½ Senepol x ½ Nellore (S), were randomly assigned in two NP on growing phase: mineral (M) or concentrate (C, energy protein 0.3% BW). Following the growing phase, two replicates within each treatment were randomly assigned to one of two finishing systems: pasture (P, n = 59) and conventional feedlot (CF, n = 60). Bulls were supplemented daily with 2% BW of concentrate (16% CP and 78% TDN) and slaughtered at a commercial abattoir. Steaks from longissimus muscle (LM) between 12(th) and 13(th) ribs each animal were collected for analysis of concentration myoglobin (MYO) and subcutaneous fat were removed for color analysis (parameters: L*, a*, b*, C* and h*). The data were analyzed by ANOVA using PROC MIXED procedures in SAS 9.4, with a 3×2×2 factorial arrangement. The muscle of Nellore showed greater (P = 0.006) concentration of MYO compared to Angus, however, Senepol had values similar to Nellore and Angus (4.43, 4.03 and 4.25, Nellore, Angus, and Senepol, respectively), and the muscle of animal finished on CF had lower concentration of MYO compared to pasture (P < 0.0001; 4.55 and 3.93, P and CF). The subcutaneous fat of animals finished on pasture showed high (P < 0.05) of L*, a*, b* and C* compared to CF. Therefore, the meat quality parameters were more affected by finished systems, the meat of animals from pasture had the lighter fat and amount of yellow pigmentation, and also presented meat with greater level of myoglobin.